Language Indigenization in Terms of Language Contacts (Based on the Nigerian English Variant) - Baghana, Jerome; N. Prokhorova, Olga; V. Chekulai, Igor; G. Voloshina, Tatiana; A. Sheyfel, Natalia (International Journal of Criminology and Sociology, 2022)
The purpose of the article is to identify the specifics of the English language Indigenization procedure on the territory of Nigeria, one of the largest countries in West Africa. The research work has the complex system to analyze the cultural and linguistic processes, which are manifested in the study under the influence of cultural factors and its influence on the language functioning. The practical work part is based on the analysis of the language thematic groups “National food” and “National clothes” presenting the specific features of Nigerian English. The results show, Nigerian English has a wide range of words denoting local realities and reflecting the adaptation of the English language to the Nigerian culture peculiarities, which are the process of indigenization. All in all, English words with new lexical meanings, words from Nigerian languages, and Portuguese loanwords have been used for naming local food and clothing elements.